Pemberdayaan Ibu Hamil Trimester III melalui Edukasi Tanda Bahaya Kehamilan dan Gizi untuk Pencegahan Stunting di Desa Domas Pontang - Nurseha, Nurseha; Subagio, Sri Utami; Aisyiyah, Nani (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
This community service aims to improve the knowledge of pregnant women in the third trimester regarding danger signs and nutrition in Domas Pontang Village. The intervention was carried out through a 120-minute face-to-face counseling session, using educational leaflets and lecture-based presentation media. A total of 25 pregnant women participated in the activity. The pre-test and post-test scores showed changes in the form of an increase in the number of participants who understood (40%) during the pre-test, then there was an increase in the number of participants who understood, namely (100%) during the post-test. Conclusion: There was an increase in the knowledge of pregnant women in the third trimester regarding danger signs and nutrition. Keywords: pregnant women, knowledge, danger signs, nutrition, community empowerment